Pricing on Consumer Purchasing Decisions at Coffee Shop in East Jakarta - Tanjung Prasetyo; Muhamad Ramadhani; Muhamad Ardan (Jurnal Ilmu Manajemen dan Ekonomika, 2023)
The purpose of this study was to analyze the effect of pricing on purchasing decisions at the East Jakarta Bro and Brew coffee shop. Quantitative descriptive is the method used in this research. The population is 6,800 consumers at the Bro and Brew coffee shop and 100 consumers are respondents who use the Slovin formula. The questionnaire as a container for obtaining primary data for this study used a Likeart scale using the SPSS version 26 program, namely the reliability test of the model with the Cronbach Alpha formula, a simple linear regression data analysis technique. The results of testing the hypothesis obtained a positive slope value of 3.461, which means that there is a significant influence between price on consumer purchasing decisions with an influence level of 80%, it can be said that the price hypothesis test influences consumer decisions (Ho is rejected) at the Bro and Brew coffee shop, East Jakarta.